The Optimation of Shrimp Shells Demineralisation, Deproteinisation, and Deasetilation on Water Soluble Chitosan Production - Rizal Alamsyah; Susi Heryani; Irma Susanti (Warta Industri Hasil Pertanian, 2012)
Shrimps shell still considered a solid waste (solid waste) and the problem of environmental pollution. Shrimp shell processing into high value-added products such as chitin and chitosan water soluble can expand its application in user industries. This study was aimed to obtain optimal condition for shrimp shells which resulted from quick frozen shrimp into water soluble chitosan (WSC). Stage of the process was conducted on the extraction of chitin (demineralization and deproteinasi), extraction of acid-soluble chitosan (ASC) (deacetylation), and manufacture of water-soluble chitosan. Demineralization of shrimp shells performed using 1 N HCL, the ratio (1:4), at a temperature of 70-75 C. Deproteinisasi performed using NaOH 3.5%, ratio (1:4) at a temperature of 80-85 C, the results of the deproteinisasi is chitin. Extraction of chitosan (deacetylation process) is done using NaOH 50%, ratio (1:20) at a temperature of 120-140 C. Demineralization, deproteinization, and deacetilation were conducted for 4 and 6 hours. One treatment was also conducted to produce ASC by applying directly deacetilation NaOH 50% at 140 C without demineralization and deproteinization. For the WSC stage, ASC producd was then mixed with DMAc (dimethyl acetate), stored (for aging), separated, washed, dried, and blended. The best treatment is demineralization process step, deproteinisasiand deacetylation for 4 hours, which ASC yield of 28.33% and WSC 15.46%. As for the process of direct deasetilisasi, produced the greates chitosan. The best characteristics of WSC was expressed in term of solubility (5 mg WSC/250 mL water), moisture content (10,0%), mineral or ash content (0.16%), nitrogen content (2.11%), viscosity (6 cps), and degree of deacetylation (64,75%).